Human security : is the best way to ensure the security of the people in Myanmar? - Aye Thet Mar (2008)
The notion of human security has emerged as a new security paradigm in the agenda of security studies since the end of the Cold War. It emphasizes on the basic rights and needs of human beings and it creates a condition in which people can enjoy fully their abilities and opportunities. This dissertation is exploring whether the notion of human security would be suitable to practice in the country like Myanmar, in which the regime's security concept is largely concerned with the traditional state-centric security perspective in terms of 'national security'.